Carbon dot-based treatment for bacterial pneumonia by promoting a PI3K-mediated M1 polarization of macrophages - Xuan Jiang; Jun Wang; Lin Gan; Zengshuai Wu; Tong Wu; Fengyang Li; Xiaowei Xu; Liancheng Lei; Na Li (Journal of Nanobiotechnology)
Abstract As the incessant emergence of drug-resistant bacterial strains, bacterial pneumonia poses a serious threat to the public health worldwide. There is an urgent need to explore unconventional therapeutic strategies. Carbon dots are usually designed to directly kill bacteria, however, carbon dots that enhance the anti-infection function of immune cells are rarely reported. In the present study, CDots were synthesized with ascorbic acid and polyethyleneimine, exhibiting outstanding biocompatibility. Functionally, the CDots exhibited a well therapeutic impact on bacterial pneumonia induced by gram-positive multidrug-resistant Staphylococcus aureus (MRSA) or gram-negative Klebsiella pneumoniae (K. pneumoniae) in mice. Utilizing in vitro models of macrophages infected with MRSA and K. pneumoniae, we discovered that CDots augmented the M1 polarization of macrophages, subsequently enhancing their survival and activity of phagocytosis and bactericidal. Further investigations through molecular dynamics simulations and in vitro experiments validated that CDots directly bind to the catalytic subunit (PIK3CD) of phosphoinositide 3-kinase (PI3K), resulting in the inhibition of the PI3K/AKT/mTOR signaling pathway. Moreover, the crucial domain for the binding was located in amino acids 752–787 of PIK3CD. In summary, CDots exerted a protective effect on bacterial pneumonia by targeting the PIK3CD and fostering the PI3K-mediated M1 polarization of macrophages. These findings not only reveal a new role of CDots in the treatment of bacterial pneumonia, but also provide potential targets for future treatment strategies. Graphical Abstract